Baicalein, a Component of Scutellaria baicalensis, Attenuates Kidney Injury Induced by Myocardial Ischemia and Reperfusion - Lai, Chang-Chi; Huang, Po-Hsung; Yang, An-Han; Chiang, Shu-Chiung; Tang, Chia-Yu; Tseng, Kuo-Wei; Huang, Cheng-Hsiung (Planta Medica, 2016)
Acute kidney injury is a common and severe complication of acute myocardial infarction and cardiac surgery. It results in increased mortality, morbidity, and duration of hospitalization. Baicalein is a component of the root of Scutellaria baicalensis, which has traditionally been used to treat cardiovascular and liver diseases in Asia. In this study, we investigated whether baicalein can attenuate kidney injury induced by myocardial ischemia and reperfusion in rats. Myocardial ischemia and reperfusion, induced by a 40-minute occlusion and a 3-hour reperfusion of the left anterior descending coronary artery, significantly increased blood urea nitrogen and creatinine levels in addition to causing histological changes in the kidneys. Kidney apoptosis was also significantly increased. Furthermore, myocardial ischemia and reperfusion significantly increased the serum levels of tumor necrosis factor-α, interleukin-1, and interleukin-6 as well as the tumor necrosis factor-α levels in the kidneys. Intravenous pretreatment with baicalein (in doses of 3, 10, or 30 mg/kg), however, significantly reduced the increases in the creatinine level, renal histological damage, and apoptosis induced by myocardial ischemia and reperfusion. In addition, the increases in the serum levels of tumor necrosis factor-α, interleukin-1, and interleukin-6, and of tumor necrosis factor-α in the kidneys were significantly reduced. Western blot analysis revealed that baicalein significantly increased Bcl-2 and reduced Bax in the kidneys. The phosphorylation of Akt and extracellular signal-regulated kinases 1 and 2 was also significantly increased. In conclusion, baicalein significantly attenuates kidney injury induced by myocardial ischemia and reperfusion. The underlying mechanisms might be related to the inhibition of apoptosis, possibly through the reduction of tumor necrosis factor-α production, the modulation of Bcl-2 and Bax, and the activation of Akt and extracellular signal-regulated kinases 1 and 2.
Keywords: Scutellaria baicalensis; Lamiaceae; acute kidney injury; apoptosis; baicalein; myocardial ischemia and reperfusion; prosurvival kinases